An enhanced krill herd optimization technique used for classification problem - Al-Mashhadani, Firaz N.; Alsaffar, Qusay S.; Al-Jadir, Ibrahim A. (Scientific Review Engineering and Environmental Sciences (SREES), 2021)
In this paper, this method is intended to improve the optimization of the classification problem in machine learning. The EKH as a global search optimization method, it allocates the best representation of the solution (krill individual) whereas it uses the simulated annealing (SA) to modify the generated krill individuals (each individual represents a set of bits). The test results showed that the KH outperformed other methods using the external and internal evaluation measures.